(untitled) (Global Journal of Management and Business Research, 2020)
The firm is the driving force of the economy since the activities of the firms boost aggregate demand as well as aggregate supply but it is the performance of the financial system which facilitates or restricts the activities of the firms. Financial systems allocate resources from savers to investors and since these two groups have different liquidity-risk-return characteristics, financial institutions and financial markets have to issue securities and innovate to bridge the gap. The demand multiplier (together with the investment accelerator) and the credit cycle create a cyclic growth process which needs to be stabilized from context to context through rule based activist monetary policy and regulation when there are fiscal constraints. Inequality and imperfections of financial markets reinforce each other making policy innovations necessary but liberalization of the economy may go a long way in reducing inequality and poverty.